2018
DOI: 10.1177/0011000018792669
|View full text |Cite
|
Sign up to set email alerts
|

Atheism as a Concealable Stigmatized Identity: Outness, Anticipated Stigma, and Well-Being

Abstract: In a preliminary exploration of atheists using a concealable stigmatized identity framework, we investigated outness, identity magnitude, anticipated stigma, and psychological and physical well-being. Atheists (N = 1,024) in the United States, completed measures of outness, atheist identity magnitude, anticipated stigma, and psychological and physical wellbeing online. Consistent with predictions, we found small but significant associations between (a) anticipated stigma and well-being, (b) social components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 63 publications
8
59
0
Order By: Relevance
“…Indeed, the methods for quantifying intersectionality are largely not agreed upon (see Else‐Quest & Hyde, ). In addition, in determining CSIs, participants were provided a researcher‐generated list of possible identities to check off (see Table ), and therefore we may not have captured every CSI that every participant possessed or was important to them (e.g., [non]religious identification; Abbot & Mollen, ). Finally, our sample was predominantly White, educated, and, as this research was conducted through online collection systems, internet savvy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the methods for quantifying intersectionality are largely not agreed upon (see Else‐Quest & Hyde, ). In addition, in determining CSIs, participants were provided a researcher‐generated list of possible identities to check off (see Table ), and therefore we may not have captured every CSI that every participant possessed or was important to them (e.g., [non]religious identification; Abbot & Mollen, ). Finally, our sample was predominantly White, educated, and, as this research was conducted through online collection systems, internet savvy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ingroup-related aspects of atheist identification were associated with higher physical and mental well-being among atheists [53].…”
Section: The Psychology Of Nonbelieversmentioning
confidence: 91%
“…Gervais's research also provides a potential solution for this prejudice—a perception that atheism is widespread (Gervais ). This finding has led to initiatives among secular groups for more atheists to “come out” (Abbott and Mollen ), under the assumption that contact with atheists and other nonbelieving or nonreligious individuals will reduce prejudice toward those who fall within religion's other (Allport ).…”
Section: Prejudice and Discriminationmentioning
confidence: 99%
“…A few studies have examined another side to the issue of prejudice and the social stigma that atheists and other nonreligious individuals face: how they differentially conceal, disclose, and manage this stigma and negotiate relationships with family, friends, and others. For instance, Abbot and Mullen's () study of atheists found significant associations between their anticipation of social stigma, their level of openness, and their psychological well‐being. Scheitle et al.…”
Section: Prejudice and Discriminationmentioning
confidence: 99%